Correction of chin ptosis. Issue 8 (August 2017) - Torrealba, R.; Fariña, R.; Valladares, S.; Sáez, F.
Abstract: Chin ptosis is described as a descent of the soft tissue from the symphyseal region to a position under the lower contour of the mandible. Given its multifactorial causes, treatment must be determined on a patient-by-patient basis. While augmentation of the submental crease is a versatile option for the correction of chin ptosis, this only corrects the soft tissue component. A technical modification to treat dynamic chin ptosis, associated with bone reduction in the mandibular symphysis, is presented here.